LGBT, Muslim, and Heterosexism: The Experiences of Muslim Gay in Indonesia - Anan Bahrul Khoir (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2020)
Muslim gay and bisexual men have been facing various challenges when living in a homophobic and heterosexist society in Indonesia. However, the study of strategies they utilised to manage those homophobic attitudes, such as discrimination, prejudice, and stigma, of their sexual minority status is limited. Therefore, drawing on minority stress theory, this study explores the life experiences of Muslim gay or bisexual men in Indonesia, by focusing on the problems they faced and the strategies they used to address those issues. All participants aged between 20 and 27 years old, have self-identified as gay or bisexual men, Muslims or ex-Muslims, and have been living in Indonesia. The primary data collection was a semi-structured qualitative interview. The data were recorded and transcribed verbatim according to the research questions from a snowball sample of seven participants. The data were then analysed using thematic analysis. The study revealed that all the participants experienced sexual and religious related problems because of living in a homophobic society. These obstacles came in many forms, such as rejection, feelings of isolation and loneliness, and concerns. However, they employed strategies to solve problems, such as self-acceptance, self-control, positive reinterpretation, seeking social support, concealing, conversion, and migration. This study recommends those who support sexual minorities to help and support them in various ways, such as providing psychological services and counsellings.